Winter according to Humphrey - Birney, Betty G (New York : G.P. Putnam's Sons, 2012)
Humphrey the hamster and the students in Mrs. Brisbane's class get ready for the holidays and a special Winter Wonderland program
Ages 7-10
Keywords: Schools -- Juvenile fiction; Hamsters -- Juvenile fiction; Winter -- Juvenile fiction; Holidays -- Juvenile fiction